Pemerkayaan Literasi Aspek Yuridis, Keuangan Dan Pemasaran Usaha Pada Pegiat UMKM di Desa Tirem - Umar Burhan; Muhammad Ainul Yaqin; A Maya Rupa Anjeli; Suharto (Lembaga Dongan Dosen, 2023)
Entrepreneurship training for Micro, Small and Medium Enterprises (MSME) activists in Tirem Village, Sittingsampeyan District, Gresik Regency focuses on enriching literacy in order to develop the businesses of MSME activists so that they play an active role in expanding employment opportunities, increasing competitiveness and being export-oriented, meanwhile business elaboration The micro scale is aimed at leveraging community income, especially those with low incomes, especially in agricultural and fishing areas in rural areas. This service activity was held offline, involving 37 participants, including MSME activists in the Tirem Village environment. This activity was carried out smoothly according to schedule. Training and discussion are the methods chosen in this activity, with material on business permits, finance and business marketing for MSME activists. The output of this activity is an increase in the participants' understanding of how to independently apply for a business permit (NIB), manage business finances appropriately and analyze business marketing, so that business continuity and income can increase.